An Ecomorphological Approach to Craniomandibular Integration in Neotropical Deer - Cassini, Guillermo Hernán (2021)
South American cervids have a relatively recent evolutionary history in the Neotropics. Present taxonomical richness includes six genera and 17 species grouped in at least two clades, Blastocerina and Odocoileina. With few exceptions, functional morphology or ecomorphological approaches have not been rigorously applied to the masticatory apparatus of Neotropical deer. In order to understand the relationship between craniomandibular integration and feeding behavior, we used geometric morphometric methods (3D landmarks) to quantify the strength and significance of the correlation between morphology and feeding behavior. Two blocks Partial Least Squares analyses, angular comparison, regression analysis, and independent contrast were performed to explore the patterns of covariation between cranial and mandibular shape and size, and between them and continuous dietary characters. The main variation in shape is related to a gradient from a brachycephalic cranium with a robust mandible in small deer to a dolicocephalic cranium with a gracile mandible in large deer. These shape changes seem to be modeled by a complex interplay of allometric trends and biomechanically significant features related to the proportions of dietary monocotyledon, fruit, or dicotyledonous plant material. We find remarkable convergences in the brocket deer ecomorphotype in the two clades of Neotropical cervids, as well as similar craniomandibular traits between marsh and pampas deer with African mixed feeder bovids related to monocotyledon consumption. These findings lead us to share Radinsky’s interest in convergences in the masticatory apparatus of herbivorous mammals.